Urban heritage regeneration: Parit Buntar as walkable town, Perak / Zam Harirah Mohd Sayuti - Mohd Sayuti, Zam Harirah (2023)
Parit Buntar shares a border with Bandar Baharu in Kedah and Nibong Tebal in Penang. It was named after the legendary Tok Buntar, a leader from the past, who along with his followers constructed Sungai Kerian ditches to allow water to flow into the rice fields. Previously, it was called Parit Tok Buntar, the ditch is now referred to simply as Parit Buntar. Parit Buntar is classified as an urban heritage site as it includes a variety of cultural relics that are present in urban settings. including historical sites, locally built structures, historic landscapes, social rituals, and festive occasions. According to the site studies, a threat of historical buildings depletion and disrupted pathways with poor green infra services have been identified. The objectives of this study are to enhance Parit Buntar's unique historical significance to develop functional spatial designs that benefit users by promoting a placemaking approach and to improve the quality of the pedestrian environment towards achieving a safe walkable town. Old bui I dings serve as witnesses to a city's aesthetic and cultural heritage, fostering a sense of place and a connection with the past. Historic structures frequently serve as symbols of something notable or significant to both locals and tourists. The study employs qualitative method which consists of primary and secondary data. To conclude, the goal of this project is to enhance Parit Buntar's historical significance by connecting people and places towards a safe walkable town.